ECONOMIC, FINANCIAL, AND STRUCTURAL PERFORMANCE AND THE COVID-19 PANDEMIA IMPACTS: A CASE STUDY IN THE HOTEL SECTOR OF RS - BRAZIL - da Silva, Kalebe Galvani; de Souza, Luciana Moro; Seibert, Rosane Maria; Salla, Neusa Maria da Costa Gonçalves; Klaic, Igor Alexandre (Seven Editora, 2026)
The study aimed to analyze the economic and financial performance of a company in the hotel sector located in Northwest Rio Grande do Sul, using economic, financial, and structural indicators for the period from 2018 to 2024. Initially, a theoretical framework aligned with the research objectives was developed. Regarding its goals, the methodology was exploratory, descriptive, and applied; concerning its means, it was a documentary and case study based on accounting data provided by the company. Subsequently, economic, financial, and structural indicators were calculated, followed by quantitative and qualitative analyses that enabled an understanding of the company’s performance before, during, and after the COVID-19 pandemic. The main research results demonstrated that the analysis of indicators revealed satisfactory liquidity levels, indicating good solvency capacity, and controlled debt, capable of sustaining economic-financial equilibrium. Turnover showed a sharp decline in 2020 due to restrictions imposed by the COVID-19 pandemic but evidenced a gradual recovery in the following years analyzed. The pandemic significantly impacted revenue, gross profit, and operational activity between 2020 and 2021; however, in 2022, a strong recovery was observed, driven by the resurgence of demand. For future research, the study suggests comparisons with other hotels in the region, analyses during crisis periods, and investigations into organizational adaptation strategies in the face of uncertain scenarios.